2013
DOI: 10.1177/0731948713507264
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Explicit and Direct Generative Strategy Training and Working Memory on Word Problem-Solving Accuracy in Children at Risk for Math Difficulties

Abstract: The purpose of this study was to investigate the effectiveness of explicit, direct, and generative strategy training and working memory capacity (WMC) on mathematical word problem-solving accuracy in elementary schoolchildren. In this study, children in third grade (N = 82) identified as at risk for math difficulties (MD) were randomly assigned (within classrooms) to one of three treatment conditions that explicitly directed students’ attention to different propositions within word problems—paraphrase question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
(45 reference statements)
2
27
1
1
Order By: Relevance
“…In general, when considering the total sample, the findings complement previous studies (Moran et al., ; Swanson et al., , ) finding that paraphrasing treatments that focus on relevant propositions within the context of text with increasing irrelevant propositions are generally effective in facilitating math problem‐solving accuracy. The present study qualifies these findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In general, when considering the total sample, the findings complement previous studies (Moran et al., ; Swanson et al., , ) finding that paraphrasing treatments that focus on relevant propositions within the context of text with increasing irrelevant propositions are generally effective in facilitating math problem‐solving accuracy. The present study qualifies these findings.…”
Section: Discussionsupporting
confidence: 82%
“…The primary purpose of this study was to investigate the effectiveness of paraphrasing interventions on word problem‐solving accuracy in children who are English language learners at risk or not at risk for math difficulties (MD). Previous studies have shown that paraphrasing relevant propositions yielded positive outcomes relative to the control condition for children with and without MD (e.g., Moran et al., ; Swanson et al., , ). Because the majority of intervention studies for problem solving in children at risk for MD have shown gains only on experimental measures (e.g., Powell, ), the posttest outcomes in this study are important since they occurred on norm‐referenced tests.…”
Section: Discussionmentioning
confidence: 94%
“…Swanson et al . () reported, for example, that children with math difficulties, but an adequate WM capacity, obtained larger gains after a training programme based on the use of general heuristic strategies (e.g., distinguishing relevant from irrelevant information) and the construction of visual schema (for similar results, see also Swanson, ; Swanson, Moran, Lussier, & Fung, ). The above‐mentioned study focused on teaching and repeatedly practicing with a given strategy, and therefore, as Swanson et al .…”
Section: Discussionmentioning
confidence: 87%
“…First, visual strategy conditions yielded signifi cantly higher outcomes on normed referenced post-test problem solving measures relative to other conditions for children with MD, but these effects were isolated to those children with higher WMC. Second, our studies have yielded transfer to WM (operation span in this case) and calculation measures (e.g., Swanson 2014 ;Swanson, Moran, Lussier, & Fung, 2014 ). Effect sizes between treatment (visual-spatial strategies) and control conditions have been substantially larger on measures of operation span than measures of problem solving and calculation.…”
Section: Working Memory Capacity and Strategy Interactionsmentioning
confidence: 94%